Situation awareness in medical practice - Higham, H (2019)
Situation awareness (SA) is a cognitive skill which has been studied extensively in military and industrial settings. Recent studies have shown that errors in SA commonly underpin adverse incidents in healthcare but there is little data to improve our understanding of how to measure or improve SA in clinical settings. The aim of this thesis was to draw attention to the importance of SA in healthcare and to provide insights into how we might better train multidisciplinary teams in acute care settings. Error in healthcare and research into SA were reviewed and a novel, holistic method for the analysis of the role of SA in the evolution of error in an acute care setting was devised. A systematic review of tools for the measurement of non-technical skills (NTS) was undertaken and this informed a study to assess the reliability and usability of such tools in the measurement of SA. The final study involved the analysis of a variety of different techniques for the measurement of SA in teams from adult intensive care (AICU). The results revealed that SA errors were present in 96% of serious incidents in a large teaching hospital in the NHS. Challenges were highlighted in the measurement of NTS in healthcare including: 76 measurement tools, revealed by the systematic review, with great variability in quality of design and psychometric testing; low levels of reliability amongst expert raters using these tools and limited evidence of validity for direct and indirect measures of SA in simulated scenarios for teams from AICU. This work has revealed that SA errors are common in acute care settings and that there are significant challenges in the reliable measurement of SA. Future work should focus on improving measurement of SA and intelligent targeting of teamwork training which highlights the importance of SA and forms part of a system wide safety strategy in the NHS.